UJI KARAKTERISTIK BAJA TULANGAN BETON DI PASARAN KOTA KENDARI BERDASARKAN PERSYARATAN SNI 07-2052-2002 DAN PENGARUHNYA TERHADAP KAPASITAS TAMPANG BALOK BETON BERTULANG - Mustika, Wayan; Fitriah, Fitriah (Universitas Halu Oleo, 2018)
Steel product circulating in marketing especially in Kendari City marketing there is any kinds of type, steel that is visually doesn't fulfill diameter scale and length also many circulating in marketing, but quality of steel is not only measured with length and the diameter only, needs further assaying about nature and steel characteristic between by it to refer to Indonesian Standard (SNI) for stell product which is new that is SNI 07-2052-2002. This research aim to investigate scale (weight, diameter and cross-area), knows mechanical properties (molten strain, strength draws and strain), analyses scale (weight, diameter and cross-area) and mechanical properties (molten strain, strength draws and strain) based on standard SNI 07-2052-2002, and know influence result of inspection of molten strain (fy) to reinforced concrete beam cutting capacities.Result of inspection of scale property (diameter, heavily and cross-area) for all sample applied in research to indicate that most of sample has fulfilled the scale property except one of sample with sample code RM doesn't fulfill diameter scale and weight according to clauses of SNI 07-2052-2002. Result of inspection of mechanical properties (molten strain (fy), strength draws (fmaks) and strain (?)) indicates that all sample applied fulfills clauses of SNI 07-2052-2002, result of analysis to molten strain influence (fy) result of assaying to reinforced concrete beam cutting capacities indicates that nominal moment (Mn) happened at specimen result of assaying with molten strain (fy) showing each the happening of improvement of nominal moment (Mn) if it is compared to nominal moment (Mn) with molten strain (fy) a minimum of based on SNI 07-2052-2002